PENINGKATAN KEMAMPUAN KOORDINASI MATA DAN TANGAN ANAK USIA 4-5 TAHUN MELALUI PERMAINAN TRADISIONAL CONGKLAK DI TK TRISULA PERWARI KAYUAGUNG - Rasmitah, Diah Rayhanah; Yin Yin Septiani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to improve eye-hand coordination in children aged 4-5 years through the traditional game of congklak. The results of initial observations indicate that the child's eye-hand coordination ability is still not balanced, during sensory activities such as holding writing tools, and adjusting eye and hand movements, then because it is still early school and still needs introduction and guidance on writing tools and how to use them. This study uses a Classroom Action Research (CAR) approach in two cycles, involving 16 children as subjects. Data were collected through observation using checklist sheets, and documentation. The results showed a significant increase in the child's eye-hand coordination ability which initially reached 6.25%, increased to 12.5% in the first cycle of action, and in the second cycle increased to 56.25% in the Very Good Development (BSB) category. The results of the study above can be concluded that through the traditional game of congklak can improve children's eye-hand coordination ability, encourage children's social interaction, and train children's independence.